THE DAILY MAIL AND THE REBIRTH OF POPULIST JOURNALISM - Utomo, Wisnu Prasetya (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2022)
This paper looks at the phenomenon of populist journalism using the Daily Mail in the UK as a case study. Borrowing the concept of mediatization from Couldry and Hepp (2017) and hybridity from Chadwick (2017), this paper elaborates populist journalism as an inseparable part of the rise of populism in various places. While the socio-political context is relatively new, the historical traces of populist journalism can be traced to the phenomenon of tabloid journalism that has emerged since the early 19th century. In other words, populist journalism is a new style of developing tabloid journalism as a consequence of structural changes in the media environment.  To cite this article (7th APA style): Utomo, W. P. (2022). The Daily Mail and the rebirth of populist journalism. Journal Communication Spectrum: Capturing New Perspectives in Communication 12(1), 29-39. http://dx.doi.org/https://doi.org/10.36782/jcs.v12i1.2204